Study of contact dermatitis due to topical medicaments and cosmetics by patch testing - Vij Amit; Murthy P; Ravindra K (Wolters Kluwer Medknow Publications, 2007)
Background: Contact dermatitis is the most common immunological disorder encountered by the dermatologist and it arises when a person develops delayed type of hypersensitivity reaction to a substance coming in contact with his skin. The patch test is at present a helpful test for demonstrating contact type of allergy that identifies the cause of allergic contact dermatitis. Aim: To study the common topical medicaments and cosmetics capable of producing contact dermatitis and value of patch testing in these situations. Materials and Methods: One hundred patients suspected of having contact sensitivity to topical medicaments and common cosmetics were subjected to patch testing with the finished commercial product being used by the patient and the antigens of the Indian Standard Series and Cosmetic series kit. Results: Positivity with patch test of 96.65% was observed in patients with contact dermatitis to topical medicaments, whereas 85% of the patients with cosmetic dermatitis were tested positive. Among the cases with contact dermatitis to topical medicaments, Neomycin was tested positive in more number of patients and among the patients with cosmetic dermatitis; Kum-Kum powder and Fairness cream were tested positive in more number of patients. Conclusion: It is well known that topical medicaments are known to produce contact dermatitis; the cosmetics that are claimed to be very safe by their manufacturers do not stay much behind in doing so.